Hermetia illucens larva (Diptera: Stratiomyidae) meal as a protein ingredient for partial replacement of soybean meal in the feed of Cavia porcellus (Guinea pig): effect on the consumption, weight gain and feed conversion - Reátegui, J. (2020)
One way to address food safety and feed production is through the rearing of insects that exhibit a small ecological footprint, high growth and reproduction rates, high levels of protein, fat and minerals. Forty growing guinea pigs were fed to evaluate the effects of isonitrogenated and isoenergetic diets in which different proportions of soybean meal (0%, 16%, 32% and 50%) were replaced with Hermetia illucens meal, evaluating feed consumption/day (g/day), total feed intake (g), final body weight (g), total weight gain (g) and feed conversion index. The trial was conducted in a repeated measures Analysis of Variance with Greennhouse-Geisser correction. Crude Protein in Hermetia illucens larva meal was 42.16 ± 3.67% (dry matter), replacing soybean meal did not show statistically significant difference between daily weight gain and body weight. The 32% replacement presented a higher daily consumption: 49.05 ± 0.69 g, total consumption: 1717 ± 24.32 g and food conversion: 3.22 ± 0.07. Incorporating Hermetia illucens larva meal at 16% of the protein requirement in Cavia porcellus feeding showed a feed intake per day of 34.57 ± 0.56 and better feed conversion, 2.50 ± 0.04. Hermetia illucens larval meal is an excellent high-quality protein substitute that satisfies the nutritional requirements with less feed in guinea pigs. These findings provide information on the potential of Hermetia illucens meal as a suitable alternative source of soybean meal for guinea pig feed.